Quand l'État appauvrit les femmes. Réalités de travailleuses de soins à domicile francophones au Nouveau-Brunswick - Albert, Hélène; Savoie, Lise; Lanteigne, Isabel; Savoie, Elda; Hinse, Elyse (Revue canadienne de service social, 2019)
Résumé Cet article présente des résultats d’une recherche qualitative portant sur la fragilité des conditions symboliques et matérielles dans lesquelles le travail de soins à domicile se déploie au Nouveau-Brunswick. Dans cette province, l’État, dans le développement de politiques sociales en matière de santé et de services sociaux, souhaite que le secteur des soins à domicile devienne la pierre angulaire de son système de santé dans une volonté de maintenir des personnes âgées à demeurer à domicile le plus longtemps possible. Ce faisant le modèle de livraison de service développé repose sur une organisation qui implique l’embauche de travailleuses de soins à domicile devenant ainsi un secteur d’activités qui se caractérise par une surreprésentation féminine de la main-d’oeuvre. Au Nouveau-Brunswick, les femmes qui oeuvrent dans ce secteur sont soumises à des conditions de travail précaires qui les maintiennent dans la pauvreté. Les résultats révèlent ainsi que la précarité de ces travailleuses est accentuée par les conditions matérielles difficiles. En effet, le salaire, l’horaire de travail, les avantages sociaux, les dépenses ou les frais afférents à leur travail sont au nombre de ces conditions qui les maintiennent dans des conditions précaires. Pourtant, ces femmes jouent un rôle essentiel dans notre société, elles qui, par leur travail du care, assument des responsabilités professionnelles fondamentales au maintien du lien social. C’est donc tout un système qui est complice de l’appauvrissement de ces femmes, tout un système qui n’offre à ces dernières, ni la reconnaissance matérielle, ni la reconnaissance symbolique de leur contribution. Mots-clés : Pauvreté, femmes, soins à domicile, care, travailleuses pauvres, non reconnaissance Abstract This article presents the results of a qualitative research focusing on the fragility of the symbolic and material home health care work conditions in New Brunswick. In the context of health care and social service policy development in the province, the government wishes to establish the home health care sector as the cornerstone of the province’s health care system with a view to keeping seniors at home as long as possible. In so doing, the service delivery model developed involves hiring home caregivers, thus creating female overrepresentation in this activity sector. In New Brunswick, women working in this sector are subject to precarious working conditions that keep them in poverty. Findings reveal that women workers’ insecurity is exacerbated by difficult material conditions. Pay, work schedule, social benefits, and work-related expenses and costs are among the factors perpetuating their precarious condition. And yet, these women play a crucial role in society inasmuch as through the caregiving service that they provide, they assume professional responsibilities that are essential to maintaining social bonds. Consequently, an entire system is complicit in these women’s impoverishment, an entire system withholds the material and symbolic recognition of their contribution. Keywords: Poverty, women, home care, care, poor women workers, non-recogniti

Soins à domicile en français. Rapport final - Atlantic Evaluation Group Inc (2013)

Recruiting doctors from and for underserved groups: Does New Brunswick's initiative to recruit doctors for its linguistic minority help rural communities? - Beauchamp, Jacinthe; Bélanger, Mathieu; Schofield, Aurel; Bordage, Rachel; Donovan, Denise; Landry, Michel (Canadian Journal of Public Health / Revue canadienne de santé publique, 2013)
Objectives Within health care, there are underserved groups. New Brunswick’s French-speaking minority, which also mostly lives in rural communities, is one such group. A physician shortage potentially prevents this population from accessing health promotion and clinical prevention services. This study analyzes whether New Brunswick Francophone doctors with rural backgrounds are more likely than doctors from urban regions to set up practice in rural communities of the province. Methods A questionnaire was sent to 390 New Brunswick Francophone physicians admitted in medicine between 1973 and 2000. It collected information on geographic origin and history of medical practice. Multivariate logistic regressions were used to identify whether a rural background is associated with the likelihood of ever and currently practicing in rural communities. We used the General Practice Rurality Index-simplified to quantify the rurality level of communities. Results In total, 264 (67%) physicians participated. A rural background was positively associated with the establishment of a first medical practice in a rural community. This relationship was only significant among family physicians. There was no statistically significant relationship between rurality of community of origin and rurality of current community of practice among either family or specialty physicians. Conclusion Although Francophone doctors with a rural background were more likely than their urban counterparts to set up their first practice in a rural community, this effect was not sustained. This raises questions as to why they leave rural communities and highlights the importance of measures to retain doctors as a way to promote public health for underserved rural groups.

Conclusion : des connaissances nouvelles pour des services en français de qualité et sécuritaires à l’intention des communautés francophones en situation minoritaire - Bouchard, Pier; Savard, Jacinthe; Savard, Sébastien; Vézina, Sylvain; Drolet, Marie (Accessibilité et offre active : santé et services sociaux en contexte linguistique minoritaire, 2017)
Le cadre théorique en filigrane de cet ouvrage, soit le modèle de l’analyse stratégique, est repris la conclusion et contribuer à améliorer la compréhension du rôle de l’acteur et du système dans l’actualisation des principes de l’offre active de services sociaux et de santé dans la langue au choix de l’usager. Le chapitre aborde les enjeux de l'accès à des services sociaux et de santé en français, le jeu des acteurs au sein des communautés francophones en situation minoritaire, le système et les leviers d'action ainsi que les stratégies en faveur de l'offre active. Plus spécificement, on articule les principales propositions contenues dans l’ouvrage autour des six stratégies suivantes : levier juridique et politique, formation et engagement des futurs professionnels, culture organisationnelle axée sur l’offre active, leadership des acteurs sociaux et de la communauté, mesures d’attraction et de rétention des intervenants et enfin mobilisation et collaboration des acteurs. En terminant, les stratégies sont énoncées en 6 recommandatons en faveur de l'offre active de services sociaux et de santé en français en contexte minoritaire.

Conclusion: New insights into safe, quality services in official language minority communities - Bouchard, Pier; Savard, Jacinthe; Savard, Sébastien; Vézina, Sylvain; Drolet, Marie (Accessibility and active offer: Health care and social services in linguistic minority communities, 2017)

L’attraction organisationnelle et les valeurs des jeunes : le cas du personnel infirmier en milieu hospitalier - Bouchard, Pier; Vézina, Sylvain (Minorités linguistiques et société, 2015)
La prestation de services de santé de qualité aux communautés francophones soulève la question de la disponibilité des ressources humaines, des jeunes professionnels en particulier. Ainsi, les gestionnaires des établissements de santé doivent élaborer des stratégies de recrutement/rétention qui tiennent compte des aspirations et des valeurs des jeunes. À cet égard, nous présentons ici les résultats d’une enquête menée auprès d’infirmières et de gestionnaires d’un important établissement de santé francophone du Nouveau-Brunswick. Ces résultats nous amènent à proposer des pistes d’action susceptibles de favoriser l’engagement des jeunes professionnels qui deviendront les ambassadeurs de services de santé en français de qualité. Mots-clés : services de santé en français, valeurs et aspirations des jeunes, recrutement, rétention, infirmières, gestion des ressources humaines, hôpital, leadership transformationnel

Bilingual health care in Quebec: Public policy, vitality, and acculturation issues - Bourhis, Richard Y. (Accessibility and active offer: Health care and social services in linguistic minority communities, 2017)
Abstract The first part of this chapter offers the Interactive Acculturation Model (IAM), which provides an intergroup approach to minority/majority group relations in multilingual settings. The ethnolinguistic vitality framework is the first element of the IAM as it describes the relative strength and weaknesses of linguistic communities in contact. Four language policies regulating the status of linguistic communities constitute the key second element of the IAM. Third, the acculturation orientations of minority and majority group speakers are described as they interact to yield harmonious, problematic or conflictual intergroup relations. As an application of the IAM, the second part of the chapter analyzes bilingual health care policies for official language minorities in Canada and Quebec. A detailed analysis of bilingual health care institutions serving the English-speaking communities of Quebec closes with a case study of a recent Quebec Government health care law that threatened to undermine the institutional vitality of the Anglophone minority of Quebec. Key words: Interactive Acculturation Model (IAM), English-speaking communities of Quebec, health care policies.

Un regard sur la distribution des médecins de famille qui parlent français dans les communautés francophones de l’Ontario - Centre de recherche en santé dans les milieux ruraux et du nord (FOCUS sur la recherche [Université Laurentienne], 2013)

Examining the distribution of French speaking family physicians in Ontario’s Francophone communities - Centre for Rural and Northern Health Research (FOCUS on research [Laurentian University], 2013)

La pénurie de professeures de sciences infirmières au Canada et ses effets sur les programmes de formation en sciences infirmières offerts en français - Chartrand, Julie; Vandyk, Amanda; Beké, Émilie; Balasa, Rebecca; Loranger, Catherine; Muray, Mwali; Chartrand, Mariève; Baker, Cynthia (Minorités linguistiques et société, 2019)
Cette étude qualitative décrit la pénurie de professeures en sciences infirmières et ses effets actuels et potentiels sur les programmes canadiens de formation en sciences infirmières offerts en français, ainsi que les stratégies préconisées par les directrices de ces programmes afin d’en atténuer les effets. Les effets de la pénurie sont particulièrement préoccupants dans le cas des programmes offerts dans un contexte francophone minoritaire ou en région éloignée. La pénurie mettrait en péril les programmes offerts en français et menacerait, par le fait même, la qualité des services de santé offerts aux communautés francophones minoritaires au Canada. Mots-clés : pénurie professorale, sciences infirmières, professionnels de la santé, services et soins de santé en français, communautés francophones en situation minoritaire

Améliorer l’accès des personnes âgées de Saint-Boniface et de Saint-Vital aux services de santé en français. Objectif 4 - Identification des ressources humaines bilingues et des pratiques actuelles en matière de ressources humaines - de Moissac, Danielle; Ba, Halimatou; Roch-Gagné, Margaux; Gagné, M. (Université de Saint-Boniface, 2012)
Le premier volet de l’étude globale « Améliorer l’accès des personnes âgées de Saint-Boniface et de Saint-Vital aux services de santé en français », dressait un portrait des états de santé et des besoins de services des personnes ainées de ces deux quartiers. Le deuxième volet de l’étude portant sur l’identification des services de santé disponibles en français, a permis de répertorier 106 organismes des secteurs public, communautaire, privé à but lucratif et privé à but non lucratif offrant des services de santé en français à Saint-Boniface et à Saint-Vital. Les buts du présent volet sont 1) de repérer les ressources humaines bilingues pouvant servir les aînés en français au sein de ces mêmes organismes en prenant en considération tout le continuum de soins et 2) de mieux comprendre les pratiques actuelles et les défis entourant le recrutement, l’embauche et la rétention des professionnels pouvant offrir des services en français. Plus précisément, nous tenterons de déterminer le nombre et le pourcentage de professionnels pouvant offrir des services en français, d’identifier la nature des services offerts par ces professionnels bilingues, de définir les pratiques actuelles quant au recrutement et à l’embauche de personnel bilingue et de cerner les défis quant au jumelage des besoins des aînés avec les ressources humaines bilingues disponibles. Ainsi, nous disposerons d’un portrait des ressources humaines bilingues et des pratiques actuelles en matière de ressources humaines quant aux établissements désignés bilingues ou francophones, aux établissements de soins de longue durée et aux fournisseurs de soins à domicile à Saint-Boniface et à SaintVital.

Improving St. Boniface and St. Vital seniors' access to French-language health services. Objective 4 - Identification of current bilingual human ressources and human resource practices - de Moissac, Danielle; Ba, Halimatou; Roch-Gagné, Margaux; Gagné, M. (Université de Saint-Boniface, 2012)
The first part of the comprehensive study entitled “Improving St. Boniface and St. Vital Seniors’ Access to French-language Health Services,” provided an overview of the health status and service needs of seniors in these two neighborhoods. The second part, focused on identifying available French-language health services, listed 106 public, community, private forprofit and private not-for-profit and community organizations offering Frenchlanguage services in St. Boniface and St. Vital. The goals of this fourth part of the study are to: 1) identify bilingual human resources able to serve seniors in French within these organizations across the continuum of care and 2) better understand current practices and challenges in recruiting, hiring and retaining professionals who can offer French-language services. Specifically, we will attempt to determine the number and percentage of professionals who can offer French-language services, identify the nature of services offered by these bilingual professionals, identify current practices for recruiting and hiring bilingual staff and identify the challenges in matching the needs of seniors with bilingual human resources. This will provide us with an overview of current bilingual human resources and human resource practices in designated bilingual or Francophone facilities, long-term care facilities and home care providers in St. Boniface and St. Vital.

Défis associés à l’offre de services de santé et de services sociaux en français au Manitoba : perceptions des professionnels - de Moissac, Danielle; de Rocquigny, Janelle; Giasson, Florette; Tremblay, Cindy-Lynne; Aubin, Natalie; Charron, Marc; Allaire, Gratien (Reflets, 2012)
Les services de santé et les services sociaux en français ne sont accessibles qu’auprès d’un quart de la population francophone au Manitoba (de Moissac, 2011). Une pénurie de professionnels pouvant offrir des services en français est perçue comme un obstacle important pour les usagers qui recherchent ces services et pour les professionnels qui voudraient assurer un suivi en français pour leurs clients. Une hésitation à s’identifier comme francophone et un manque de connaissance des ressources disponibles en français contribuent-ils à cette perception de pénurie? Cet article traite des défis entourant l’offre de services de santé et de services sociaux en français au Manitoba et suggère des pistes de solutions. Mots-clés : disponibilité, accessibilité, minorité francophone, Manitoba, professionnels

Disponibilité et accessibilité des services de santé en français au Manitoba. Rapport final - de Moissac, Danielle; de Rocquigny, Janelle; Roch-Gagné, Margaux; Giasson, Florette (Université de Saint-Boniface et Institut franco-ontarien de l’Université Laurentienne, 2011)

Le recrutement et la rétention des professionnels de la santé et des services sociaux bilingues en situation minoritaire - de Moissac, Danielle; Savard, Sébastien; Ba, Halimatou; Zellama, Faïçal; Benoît, Josée; Giasson, Florette; Drolet, Marie (Université de Saint-Boniface et Université d'Ottawa, 2014)
Cete étude cherchait à connaitre les éléments favorisant l’engagement et la motivation des professionnels ainsi que les pratiques de gestion des ressources humaines qui encourage le personnel bilingue à s’intéresser au travail en milieu bilingue et à demeurer en poste.

Active offer of health services in French in Ontario: Analysis of reorganization and management strategies of health-care organizations - Farmanova, Elina; Bonneville, Luc; Bouchard, Louise (The International Journal of Health Planning and Management, 2018)
The availability of health services in French is not only weak but also inexistent in some regions in Canada. As a result, estimated 78% of more than a million of Francophones living in a minority situation in Canada experience difficulties accessing health care in French. To promote the delivery of health services in French, publicly funded organizations are encouraged to take measures to ensure that French-language services are clearly visible, available, easily accessible, and equivalent to the quality of services offered in English. Objective This study examines the reorganization and management strategies taken by health care organizations in Ontario that provide health services in French. Methods Review and analysis of designation plans of a sample of health care organizations. Results Few health care organizations providing services in French have concrete strategies to guarantee availability, visibility, and accessibility of French-language services. Conclusions Implementation of the active offer of French-language services is likely to be difficult and slow. The Ontario government must strengthen collaboration with health care organizations, Francophone communities, and other key actors participating in the designation process to help health care organizations build capacities for the effective offer of French-language services.

Success strategies for linguistically competent healthcare: The magic bullets and cautionary tales of active offer of French-language health services in Ontario - Farmanova, Elina; Bouchard, Louise; Bonneville, Luc (Healthcare Quaterly, 2018)
An active offer of French-language health services (FLHS) was introduced in several Canadian provinces to help create an environment that will anticipate the needs of Francophones in their community and will stimulate the demand for services in French. For the active offer to be implemented, changes in how health services are organized and managed at both organizational and system levels must be introduced. In this perspective paper, we identify several success strategies and potential pitfalls with regards to the implementation of the active offer of FLHS primarily at the level of healthcare organization. Our recommendations are based on a recent health services research study exploring reorganization and management strategies for the delivery of the active offer of FLHS in Ontario and insights from a focus group with healthcare administrators conducted as part of this research. We propose a "wrap-around strategy" called organizational health literacy to help reorient organizational culture and improve management and sustainability of the active offer of FLHS. These strategies have relevance for advocates and professionals working to promote an active offer of FLHS, including healthcare administrators, human resource professionals, quality-improvement specialists and others.

Offering health services in French: Between obstacles and favourable factors in Anglophone hospital settings - Forgues, Éric; Bahi, Boniface; Michaud, Jacques (Accessibility and active offer: Health care and social services in linguistic minority communities, 2017)

Offre de services de santé en français : entre obstacles et facteurs favorables en milieu hospitalier anglophone - Forgues, Éric; Bahi, Boniface; Michaud, Jacques (Accessibilité et offre active : santé et services sociaux en contexte linguistique minoritaire, 2017)
Résumé Notre chapitre vise à mettre en relief les facteurs sociaux et organisationnels qui favorisent l’offre de services de santé en français par des professionnels travaillant dans des établissements de santé majoritairement anglophones. Il présente une perspective sociologique qui invite les intervenants à tenir compte de la complexité de l’environnement socio-organisationnel dans lequel pratiquent les professionnels de la santé. Ainsi, leurs compétences linguistiques ne suffisent pas à assurer pareille offre. L’engagement de la haute direction et de ses gestionnaires, la gestion des services et des ressources humaines, les relations de travail, la disponibilité de la main-d’oeuvre bilingue, le contexte juridique et politique sont, entre autres facteurs, des éléments à considérer afin de comprendre dans tous ses aspects la prestation de services de santé en français. Plus largement, ils renvoient nécessairement aux rapports sociaux qu’entretiennent les anglophones et les francophones. Mots-clés : services de santé, environnement socio-organisationnel, droits linguistiques, professionnels de la santé.

L’offre de services de santé en français en contexte francophone minoritaire - Forgues, Éric; Bahi, Boniface; Michaud, Jacques; Deveau, Kenneth; Boudreau, Jonathan; St-Onge, Sylvain (Institut canadien de recherche sur les minorités linguistiques, 2011)

Examining the geographic distribution of French-speaking physicians in Ontario - Gauthier Alain P.; Timony Patrick E.; Wenghofer, Elizabeth. F. (Canadian Family Physician, 2012)
Abstract: Objective: To determine how many physicians in Ontario express a proficiency in providing services in the French language, and to assess the geographic distribution of such physicians. Design: Population-based analysis of the 2007 College of Physicians and Surgeons of Ontario Annual Membership Renewal Survey. Setting: Ontario. Participants: A total of 22688 GPs, FPs, and other specialists certified by the College of Family Physicians of Canada and the Royal College of Physicians and Surgeons of Canada who responded to the survey. Main outcome measures: First official language spoken and languages of competency to conduct practice. Results: The physician-to-patient ratio by first official language spoken is 1 physician per 138 Francophone patients in Ontario. There is 1 French-speaking GP or FP for every 297 Francophone patients, and most French-speaking physicians are located in southern Ontario (91.4%), at a ratio of 1 physician per 111 Francophone patients. The most promising French-speaking physician–to–Francophone patient ratios are found in southern Ontario (1:248 for GPs and FPs, and 1:202 for other specialists) and in urban Ontario (1:266 for GPs and FPs, and 1:209 for other specialists). Conclusion: Clearly, there is a promising number of physicians, relative to the amount of French-speaking residents in Ontario, who identified a competency in offering services in French. However, while the number of physicians who indicated a self-assessed competency to deliver health services in French is promising, it is the maldistribution of such services that is of concern. Thus, efforts must be made to attract French-speaking physicians to areas where there is the greatest demand, particularly in the northern part of the province. Résumé Objectif: Déterminer combien de médecins ontariens se disent compétents pour fournir, des services en français et vérifier la distribution géographique de ces médecins. Type d’étude: Analyse démographique du rapport de 2007 sur la réinscription annuelle à l’Ordre des médecins et chirurgiens de l’Ontario. Contexte: L’Ontario. Participants: Un total de 22 688 omnipraticiens (OP), MF et autres spécialistes diplômés du Collège des médecins de famille du Canada et du Collège royal des médecins et chirurgiens du Canada qui ont répondu à l’enquête. Principaux paramètres à l’étude: Première langue officielle parlée et langues de compétence pour la pratique. Résultats: En Ontario, le rapport médecin/patient dans le cas de la première langue officielle parlée est de 1 médecin pour 138 patients francophones. On compte un OP ou MF francophone pour 297 patients francophones et les médecins francophones sont localisés pour la plupart (91,4%) dans le sud de l’Ontario, où on observe 1 médecin pour 111 patients francophones. C’est dans le sud de l’Ontario que le rapport médecin francophone/patient francophone est le plus favorable (1/248 pour les OP et les MF, et 1/1202 pour les autres spécialistes) et dans les milieux urbains (1/266 pour les OP et les MF et 1/1209 pour les autres spécialistes). Conclusion: Il est certain qu’en Ontario, il y a un nombre encourageant de médecins qui, par rapport au nombre de résidents francophones, se sont dits compétents pour offrir des services en français. Malgré ce rapport favorable, c’est la mauvaise distribution de ces services qui est préoccupante. Il faudrait donc s’efforcer d’attirer des médecins francophones dans les régions où la demande est la plus forte, notamment dans le nord de la province.

Barriers and strategies to offering health services to French-speaking patients: Perspectives from family physicians in Northeastern Ontario - Gauthier, Alain P.; Timony, Patrick E. (Research in FOCUS on Research [Centre for rural and northern health research], 2015)

Les obstacles et les stratégies dans les services de santé offerts aux patients francophones : perspectives des médecins de famille dans le Nord-Est de l'Ontario - Gauthier, Alain P.; Timony, Patrick E. (FOCUS sur la recherche [Centre de recherche en santé dans les milieux ruraux et du nord], 2015)

Étude exploratoire sur les compétences linguistiques à l’embauche - Gauthier, Hubert (Conseil communauté en santé du Manitoba, 2011)

Compétences linguistiques et qualité de services. Argumentaire pour des services de soins de santé en français de qualité - Gauthier, Hubert; Reid, Marc-André (Conseil communauté en santé en français du Manitoba, 2012)

Le défi de la formation universitaire des audiologistes et orthophonistes pouvant offrir des services aux francophones de l’Ontario - Lefebvre, Pascal; Marcoux, André (Éducation francophone en milieu minoritaire, 2011)
Cette étude avait pour but d’identifier les facteurs contribuant à la rétention des audiologistes et orthophonistes pouvant offrir des services auprès des francophones de l’Ontario. Une étude rétrospective comprenant des analyses descriptives et une régression logistique fut menée auprès de 192 finissants du Programme d’audiologie et d’orthophonie de l’Université d’Ottawa. Les résultats démontrent une relation significative entre le lieu de travail et quatre facteurs : le lieu de provenance de l’étudiant, la priorité du choix de l’université, la langue d’enseignement au baccalauréat, ainsi que le niveau de confiance à travailler en anglais. Les analyses démontrent également que le lieu de provenance peut fortement prédire à lui seul si un finissant du programme choisira l’Ontario comme lieu de travail. Des recommandations sont proposées concernant l’admission et la formation des étudiants de ce type de programme afin d’assurer une forte rétention de professionnels francophones en Ontario.

Health care professionals and official-language minorities in Canada, 2001 and 2011 (n°89-657-X 2017002) - Lepage, Jean-François; Lavoie, Émilie (Statistics Canada, 2017)

Professionnels de la santé et minorités de langue officielle au Canada, 2001 et 2011 (n°89-657-X 2017002) - Lepage, Jean-François; Lavoie, Émilie (Statistique Canada, 2017)

Soins de longue durée en français. Rapport final - McQuaid, Steve (The Atlantic Evaluation Group Inc, 2010)

Workforce utilization of visible and linguistic minorities in Canadian nursing - Premji, Stephanie; Etowa, Josephine. B. (Journal of Nursing Management, 2012)
Background There is ample evidence of ethnic and linguistic segregation in the Canadian labour market. However, it is unknown if there is equitable representation of visible and linguistic minorities in nursing professions. Methods We cross-tabulated aggregate data from Statistics Canada’s 2006 Census. Analyses examined the distribution of visible and linguistic minorities, including visible minority sub-groups, among health managers, head nurses, registered nurses, licensed nurses and nurse aides for Canada and major cities as well as by gender. Results In Canada and its major cities, a pyramidal structure was found whereby visible and linguistic minorities, women in particular, were under-represented in managerial positions and over-represented in lower ranking positions. Blacks and Filipinos were generally well represented across nursing professions; however, other visible minority sub-groups lacked representation. Conclusions Diversity initiatives at all levels can play a role in promoting better access to and quality of care for minority populations through the increased cultural and linguistic competence of care providers and organizations.

Affichage de postes bilingues dans la région de Kingston. Un guide utile pour les employeurs des secteurs de la santé et des services sociaux et communautaires | Job posting resource for bilingual positions in the Kingston area. A useful guide for employers in the healthcare and social community services sectors - Réseau des services de santé en français de l'Est de l'Ontario (A useful guide for employers in the healthcare and social community services sectors, 2019)

Services en français dans les CLOSM : produire des données probantes pour améliorer l’accès et la qualité. Mémoire du Réseau des services de santé en français de l’Est de l’Ontario dans le cadre de la consultation sur le renouvellement du PCLOS 2013-2018 - Réseau des services de santé en français de l’Est de l’Ontario (2016)

Guide de planification et de prestation des soins de longue durée en français. Leçons tirées du pavillon Omer Deslauriers de Bendale Acres et d'autres services de santé en français pour aînés au Canada - Réseau franco-santé du Sud de l’Ontario (2017)

Pratique # 5 : Le Cadre de référence pour le recrutement et la rétention des ressources humaines bilingues en santé et la Stratégie Ressources humaines en santé (Pan-canadien). - Savard, Jacinthe; Savard, Sébastien; van Kemenade, Solange; Benoît, Josée; Buhay, Corrina; Youbi, Sara; Kubina, Lucy-Ann (2019)

Pratique # 7 : La tournée des établissements désignés bilingues (Manitoba). Dans : GReFoPS. Répertoire de pratiques novatrices en santé et service social en langue officielle en contexte minoritaire. - Savard, Jacinthe; Savard, Sébastien; van Kemenade, Solange; Benoît, Josée; Buhay, Corrina; Youbi, Sara; Kubina, Lucy-Ann (2019)

Recruitment and retention of bilingual health and social service professionals in Francophone minority communities in Winnipeg and Ottawa - Savard, Sébastien; de Moissac, Danielle; Benoît, Josée; Ba, Halimatou; Zellama, F.; Giasson, Florette; Drolet, Marie (Accessibility and active offer: Health care and social services in linguistic minority communities, 2017)

Le recrutement et la rétention d’intervenants en santé et services sociaux bilingues en situation francophone minoritaire à Winnipeg et à Ottawa - Savard, Sébastien; de Moissac, Danielle; Benoît, Josée; Ba, Halimatou; Zellama, Faïçal; Giasson, Florette; Drolet, Marie (Accessibilité et offre active : Santé et services sociaux en contexte linguistique minoritaire, 2017)
La difficulté à recruter des professionnels en mesure d’intervenir dans les deux langues officielles a été mentionnée comme une des causes les plus importantes du manque d’accès à des services sociaux et de santé en français pour les personnes âgées francophones en situation minoritaire. Ce chapitre présente les résultats d’une recherche réalisée auprès de 55 intervenants, rencontrés dans six groupes de discussion et travaillant dans des organisations bilingues dans deux régions, soit Winnipeg au Manitoba et Ottawa en Ontario. Nous voulions connaître les facteurs ayant incité ces intervenants à vouloir travailler dans des organisations bilingues et ceux favorisant leur rétention dans les organismes où ils travaillent. Les résultats démontrent que la volonté de contribuer au mieux-être des francophones et la possibilité d’obtenir des postes stables offrant des conditions de travail intéressantes font partie des facteurs de recrutement les plus importants. La qualité du climat de travail et la possibilité de travailler dans un milieu caractérisé par la diversité sont des facteurs de rétention mentionnés régulièrement par les participants à l’étude. Une meilleure reconnaissance du fardeau supplémentaire associé au fait de travailler dans les deux langues et le recrutement de cadres bilingues font partie de recommandations permettant de faciliter le recrutement et la rétention de personnel bilingue. Mots-clés : recrutement et rétention, intervenants services sociaux et de santé, francophones en situation minoritaire.

Workload of French-speaking family physicians in Francophone rural and Northern communities in Ontario - Timony, Patrick E.; Gauthier, Alain P.; Sanou, Boroma; Wenghofer, Elizabeth. F. (Canadian Journal of Rural Medicine, 2018)
Introduction: Previous studies have shown that French-speaking family physicians (FSPs) in Ontario are less numerous in areas with high proportions of francophones. The purpose of the current study was to assess whether the degree of concordance between physicians' language of competence and the linguistic profile of the community in which they practise is associated with workload and to explore variations in this relation in rural and northern regions of the province. Methods: This was a secondary analysis of the 2013 College of Physicians and Surgeons of Ontario Annual Membership Renewal Survey. We analyzed the primary practice location and language of competence of family physicians/general practitioners. We compared the practice characteristics of FSPs and non-French-speaking physicians (NFSPs) by the proportion of the francophone population, geographic location (north vs. south) and community size (urban vs. rural). Results: Data for 10 548 family physician/general practitioners were analyzed. In areas densely populated by francophones, FSPs worked more hours per week on average and had a greater mean number of patient visits than NFSPs. Non-French-speaking physicians working in areas densely populated by francophones had fewer patient visits per hour on average than FSPs. In most cases, the results were particularly accentuated in rural and northern communities. Conclusion: Our findings suggest that, compared to NFSPs, the demands placed on FSPs are disproportionately greater in communities where the need for French-language health care services is greatest and the supply of FSPs is the smallest. Our results underline the importance of properly preparing family physicians to work in areas densely populated by francophones.

Barriers to offering French language physician services in rural and Northern Ontario - Timony, Patrick E.; Gauthier, Alain P.; Serresse, Suzanne; Goodale, Natalie; Prpic, Jason (Rural and Remote Health, 2016)
Introduction: Rural and Northern Ontario francophones face many health-related challenges including poor health status, a poor supply of French-speaking physicians, and the potential for an inability or reduced ability to effectively communicate with anglophone healthcare providers. As such, it can reasonably be expected that rural and Northern Ontario francophones experience barriers when receiving care. However, the experience of physicians working in areas densely populated by francophones is largely unexplored. This paper identifies barriers experienced by French-speaking and Non-French-speaking rural and Northern Ontario physicians when serving francophone patients. Methods: A series of key informant interviews were conducted with 18 family physicians practicing in rural and urban francophone communities of Northeastern Ontario. Interviews were analyzed using a thematic analysis process. Results: Five categories of barrier were identified: (1) language discordance, (2) characteristics of francophone patients, (3) dominance of English in the medical profession, (4) lack of French-speaking medical personnel, and (5) physicians’ linguistic (in)sensitivity. Some barriers identified were unique to Non-French-speaking physicians (eg language discordance, use of interpreters, feelings of inadequacy), some were unique to French-speaking physicians (eg limited French education and resources), and some were common to both groups (eg lack of French-speaking colleagues/staff, added time commitments, and the particularities of Franco-Ontarian preferences and culture). Conclusions: Healthcare providers and decision makers may take interest in these results. Although physicians were the focus of the present article, the barriers expressed are likely experienced by other healthcare providers, and thus the lessons learned from this article extend beyond the physician workforce. Efforts must be made to offer educational opportunities for physicians and other healthcare providers working in areas densely populated by francophones; these include linguistic and cultural sensitivity training, in addition to teaching strategies for the practice of ‘active offer’ of French-language services. In sum, the present study outlines the importance of linguistic concordant communication in healthcare delivery, and describes some of the challenges faced when providing French-language services in rural and Northern Ontario. Key words: Canada, doctor–patient communication, French-language services, key informant interviews, language concordance, language discordance, Northern Ontario, Ontario francophones, physicians.

Promising quantities, disappointing distribution. Investigating the presence of French-speaking physicians in Ontario’s rural francophone communities - Timony, Patrick; Gauthier, Alain; Hogenbirk, John. C.; Wenghofer, Elizabeth (Rural and Remote Health, 2013)
Introduction: Previous studies have suggested that there may be a lack of French language healthcare services in the province of Ontario. The purpose of this study was to determine if physicians in Ontario who expressed a proficiency in providing services in the French language are located in 'Francophone communities'. Method: Responses from 10 968 Ontario-based family physicians (FPs) certified by the College of Family Physicians of Canada and uncertified general practitioners (GPs) who responded to the 2007 College of Physicians and Surgeons of Ontario Annual Membership Renewal Survey were analysed and compared to the 2006 census of the population of Ontario. Main outcome measures were the number of FP/GPs categorized by their language of competency to conduct medical practice and the number of people categorized by their first official language spoken. The physician-to-population ratio was then compared for different groups of communities in Ontario categorized by the degree of francophonie of the community: strong French communities, with a Francophone population ≥25%; moderate French communities, with a Francophone population of 10-24%; and weak/no French communities, with a Francophone population <10%. Results: There are 5.6 French speaking FP/GPs for every 1000 Francophones in communities with a French population less than 10%. This ratio is considerably greater than what was found in moderate French communities (3.4 FP/GPs) and strong French (1.3 FP/GPs). Overall the lowest ratios were found in rural strong French communities both in southern and northern Ontario (0.8 FP/GPs and 0.9 FP/GPs respectively). The ratio for all of Ontario was 0.7-1.3. Conclusions: As the number of Francophones increases in a community, the availability of French-speaking FP/GPs actually decreases, particularly in rural northern Ontario. Furthermore, there is a paradoxical relationship between the potentially high number of FP/GPs in the province with French-language capabilities and the perceived deficiencies in the availability of French language medical services. Key words: family physician, Francophone community, general practitioners, health and human resources, language, physician-patient ratios, urban. Introduction

Knowledge and use of the English language by healthcare and social services professionals in Québec - Trempe, Normand; Lussier, Marie-Hélène (Institut national de santé publique du Québec, 2011)

La connaissance et l'utilisation de la langue anglaise par les professionnels de la santé et des services sociaux au Québec - Trempe, Normand; Lussier, marie-Hélène (Institut national de santé publique du Québec, 2011)